Analisis ‘Urf Terhadap Tradisi Naung Ri Ere Sebagai Kepercayaan Tolak Bala Pasca Pernikahan: Studi Kasus di Manipi Kecamatan Sinjai Barat Kabupaten Sinjai - Amalia, Putri; Abdul Qayyum, Abdul Rahman Hi. (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2023)
This study entitled "Urf's analysis of the factors causing the Naung Ri Ere tradition which is considered a belief in rejecting post-wedding (case study in Manipi, West Sinjai District, Sinjai Regency)" suggests several problem formulations, namely: 1). How is the process of implementing the Naung Ri Ere tradition in the community in Manipi, West Sinjai District, Sinjai Regency? 2). How is 'Urf's analysis of the factors causing the Naung Ri Ere tradition which is considered a belief in rejecting post-wedding reinforcements in the community in Manipi, West Sinjai District, Sinjai Regency? The results of this study indicate that the implementation of the Naung Ri Ere tradition is carried out in a place or river by placing offerings, reading prayers, sinking something into the water, bathing the newlyweds, and reading congratulations when returning home. The factors that influence why Naung Ri Ere is considered a belief in rejecting reinforcements a. Believing that those who do not follow the Naung Ri Ere tradition will experience misfortune and distress. b. Naung Ri Ere has always been carried out by the ancestors when the custom first entered Manipi. So it was believed from a long time ago that Naung ri Ere brings happiness to newlywed couples.